2006
DOI: 10.1086/503036
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Treatment Strategies (MIKSTRA) Program: A 5-Year Follow-Up of Infection-Specific Antibiotic Use in Primary Health Care and the Effect of Implementation of Treatment Guidelines

Abstract: Moderate qualitative improvements in antibiotic use were observed after multifaceted intervention, but prescribing for unjustified indications, mainly acute bronchitis, did not decrease. Obtained infection-specific information on management of patients with infections in primary health care is an important basis for planning targeted interventions in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 27 publications
2
52
0
1
Order By: Relevance
“…In Finland, a controlled study analysed the effect of guideline dissemination through local interactive discussion groups: no reduction in antibiotic prescription was observed during the 5-year follow-up. 36 In Switzerland, a similar lack of efficacy was reported for an interactive seminar on guidelines with and without a patientcentred communication conference. 20 However, other authors have reported more positive results.…”
Section: Comparison With Existing Literaturementioning
confidence: 72%
“…In Finland, a controlled study analysed the effect of guideline dissemination through local interactive discussion groups: no reduction in antibiotic prescription was observed during the 5-year follow-up. 36 In Switzerland, a similar lack of efficacy was reported for an interactive seminar on guidelines with and without a patientcentred communication conference. 20 However, other authors have reported more positive results.…”
Section: Comparison With Existing Literaturementioning
confidence: 72%
“…38 In Finland, a recent intervention was unsuccessful at changing the fraction of infections that were treated with antibiotics. 39 Samore et al 26 reported a decrease of 9 antibiotic prescriptions per 100 person-years using a clinical decision support system in combination with a community intervention in 12 rural communities. The current trial is unique for its exclusive focus on prescribing for children, the number of nonoverlapping communities (both urban and suburban) randomized, and the ability to compare effects among Medicaid and commercially insured children.…”
Section: Discussionmentioning
confidence: 99%
“…9 The introduction of guidelines alone has not proven to be effective at reducing antibiotic use for conditions that are, mainly, viral. 10 There is now evidence that those who consume antibiotics are more likely to become infected by organisms resistant to that antibiotic in the weeks and months following their antibiotic course. 11 There are many external (non-clinical) factors that influence a GP's decision to prescribe antibiotics.…”
Section: Introductionmentioning
confidence: 99%